HPB P24 Comparison of outcomes of Deb-TACE in patients with HCC larger than 5cm compared with HCC less than 5cm. (7th December 2022) - Youssef, Fady; Fouad, Mina; Jackson, Andrew; Hossain, Tan; Aravinthan, Aloysious; Sanyal, Sudip
Abstract: Background: Transarterial chemoembolization (TACE) improves survival in cirrhotic patients with intermediate-stage hepatocellular carcinoma (HCC). Drug-eluting bead (Deb)-TACE is associated with a reduction in liver toxicity and drug-related adverse effects compared with chemotherapy-TACE. This retrospective paired cohort study compares the outcomes of DEB-TACE in patients with HCC greater than and less than 5 centimeters. Methods: Sixty-nine patients had Deb-TACE as the primary treatment for HCC over a 3-year period from May 2019 -to May 2022. Patients were paired into two unmatched groups according to tumour size. Group A; tumour size > 5cm and group B tumour size < 5cm. Each group was then compared following a single or repeated treatment of Deb-TACE. Tumour response was evaluated using the standardised modified Response Evaluation Criteria in Solid Tumours (mRECIST) to detect evidence of tumour size regression. Patients were classified as having either a complete response (CR), partial response (PR), stable disease (SD), or progressive disease (PD). Also, any adverse outcomes including hepatic decompensation were recorded Results: Group A, (34.48%) 10 patients had a single session of Deb-TACE. Post-treatment surveillance showed that 4 patients (44.44%) showed CR, PR in 2 patients (22.22%), SD in 1 patient (11.11%), 2 patients (22.22%) had PD, one patient was still waiting for his follow-up surveillance. On the other hand, (65.52%)19 patients had repeated sessions, CR was evident in 2 patients (10.5%), PR in 1 patient (5.2%), SD in 3 patients (15.7%), PD in 2 patients (10.5%), 7 patients (36.84%) had initial PR followed by CR, 2 patients (10.5%) showed initial SD then PD and finally 2 patients (10.5%) were PR and became PD. Group B, 18 (45%) patients had single Deb-TACE, Patients showing CR were 7(58.3%), PR was detected in 2 patients (16.67%), one patient (8.33%) had SD, 2 patients (16.67%%) showed PD, and 6 patients were still waiting for their surveillance, no response recorded for them. (55%) 22 patients had repeated Deb-TACE sessions. 3 patients(13.6%) showed CR, PR were 4 patients (18.18%), one patient (4.5%) had SD, PD were 6 patients (27.27%). However, 3 patients (13.6%) were PR then showed CR, 3 patients (13.6%) were PR became PD and finally 2 patients (9%) were PD became CR. Conclusions: DEB-TACE is effective for HCCs > 5cm with a response rate of 66.67% in patients who had a Single DEB-TACE dose as their first treatment and it increased to 79% in patients who had repeated deb-TACE; however, that was not statistically significantly different (P = 0.48). The Patients group who had HCC <5 cm showed responses up to 83% with single-dose compared to 59% for repeated DEB-TACE, this was not statistically significant with (P = 0.25) . There was no difference in complications between the two groups.